Mechanical Engineering: (conference proceedings) / 10th International Conference on Sustainable Energy and Environmental Protection, (June 27th-30th, 2017, Bled, Slovenia) - Marina Bajić; Krope, Jurij; Ghani Olabi, Abdul; Goričanec, Darko; Božičnik, Stanislav (2017)
The 10th International Conference on Sustainable Energy and environmental Protection – SEEP 2017 was organised on June 27th – 30th 2017 in Bled, Slovenia, by Faculty of Chemistry and Chemical Engineering, University of Maribor, Slovenia, and University of the West of Scotland, School of Engineering and Computing. The aim of SEEP2017 is to bring together the researches within the field of sustainable energy and environmental protection from all over the world. The contributed papers are grouped in 18 sessions in order to provide access to readers out of 300 contributions prepared by authors from 52 countries. We thank the distinguished plenary and keynote speakers and chairs who have kindly consented to participate at this conference. We are also grateful to all the authors for their papers and to all committee members. We believe that scientific results and professional debates shall not only be an incentive for development, but also for making new friendships and possible future scientific development projects.
Keywords: Sustainable Energy; Environmental Protection; SEEP; International Conference; Slovenia